Cross-Border Loss Offset and Formulary Apportionment: How do they affect multijurisdictional firm investment spending and interjurisdictional tax competition? - Marcel Gérard; Joann Weiner (Center for Economic Studies and ifo Institute (CESifo), 2003)
Motivated by the EU Commissions suggested company tax reforms, this paper investigates how cross-border loss offset and formulary apportionment of a consolidated tax base affect the investment and transfer pricing behaviour of a multijurisdictional firm, and how they affect the behaviour of governments potentially engaged in tax competition. The paper shows that cross-border loss offset mitigates both the reactions of a multijurisdictional firm to tax changes and the amount of tax competition engaged in by governments. However, formulary apportionment (with a consolidated tax base) boosts the sensitivity of firms to tax changes and increases the scope for interjurisdictional tax competition as well. For governments, formulary apportionment operates like a risk-sharing or partial equalisation mechanism.
Keywords: 330; cross border loss offset; multinational firms; tax competition